The Influence Of Leadership And Human Resource Quality On Employee Performance At The Kolonodale Class Iii Port Management Office - Moh. Ilham Pratama; Andi Indriani Ibrahim; Yoberth Kornelius; Nur Riski Isliansty (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
This study aims to determine the influence of leadership and human resource quality on employee performance at the Class III Kolonodale Port Operations Unit (UPP). Employee performance is key to an organization's success in providing optimal public services. Two important factors analyzed in this study are leadership as a guide and motivator, and human resource quality, which encompasses skills, knowledge, and work attitudes. The method used in this study was a quantitative approach with data collection using a questionnaire. The population in this study was all 40 employees of the Class III Kolonodale UPP Office, who also served as a sample (census). Data were analyzed using multiple linear regression to test the simultaneous and partial effects of the independent variables on the dependent variable. The results show that simultaneously, leadership and human resource quality significantly influence employee performance. Partially, each variable of leadership and human resource quality also has a significant influence on employee performance. These findings indicate the importance of fair, communicative, and supportive leadership, as well as improving human resource quality through training and competency development, in enhancing employee performance.